Towards the development of a smart energy grid - Mahmoud M.A.; Tang A.Y.C.; Maseleno A.; Lim F.-C.; Kasim H.; Yong C. (Springer, 2023)
Electric power transmission networks; Energy efficiency; Intelligent computing; Internet of things; Renewable energy resources; Electricity networks; Electricity transmission; Literature studies; Power system; Renewable energies; Research and application; Safety and efficiencies; Smart energies; Smart power grids